How Interesting is the "Boring Problem" for Luck Egalitarianism?. (3rd August 2015) - Lang, Gerald
<x xml:space="preserve">Abstract</x> Imagine a two‐person distributive case in which Ernest's choices yield X and Bertie's choices yield X + Y, producing an income gap between them of Y. Neither Ernest nor Bertie is responsible for this gap of Y, since neither of them has any control over what the other agent chooses. This is what Susan Hurley calls the "Boring Problem" for luck egalitarianism. Contrary to Hurley's relatively dismissive treatment of it, it is contended that the Boring Problem poses a deep problem for standard luck egalitarianism. To counter it, luck egalitarianism needs to be recast as a baseline‐relative theory. This new version of luck egalitarianism is then put to work against some significant problems that have been encountered by luck egalitarianism: Saul Smilansky's "Paradox of the Baseline, " the "Partiality Worry, " and the "Pluralism Worry." But baseline‐relative luck egalitarianism is not without problems of its own.